Short-type single balloon enteroscope for endoscopic retrograde cholangiopancreatography with altered gastrointestinal anatomy - Yamauchi, Hiroshi (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate the effectiveness of a short-type single-balloon-enteroscope (SBE) for endoscopic retrograde cholangiopancreatography (ERCP) in patients with a reconstructed intestine. METHODS: Short-type SBE was developed to perform ERCP in postoperative patients with a reconstructed intestine. Short-type SBE is a direct-viewing endoscope with the following specifications: working length, 1520 mm; total length, 1840 mm; channel diameter, 3.2 mm. In addition, short-type SBE has a water-jet channel. The study group comprised 22 patients who underwent 31 sessions of short-type SBE-assisted ERCP from June 2011 through May 2012. Reconstruction was performed by Billroth-II (B-II) gastrectomy in 6 patients (8 sessions), Roux-en-Y (R-Y) gastrectomy in 14 patients (21 sessions), and R-Y hepaticojejunostomy in 2 patients (2 sessions). We retrospectively studied the rate of reaching the blind end (papilla of Vater or choledochojejunal anastomosis), mean time required to reach the blind end, diagnostic success rate (defined as the rate of successfully imaging the bile and pancreatic ducts), therapeutic success rate (defined as the rate of successfully completing endoscopic treatment), mean procedure time, and complications. RESULTS: Among the 31 sessions of ERCP, the rate of reaching the blind end was 88% in B-II gastrectomy, 91% in R-Y gastrectomy, and 100% in R-Y hepaticojejunostomy. The mean time required to reach the papilla was 18.3 min in B-II gastrectomy, 21.1 min in R-Y gastrectomy, and 32.5 min in R-Y hepaticojejunostomy. The diagnostic success rates in all patients and those with an intact papilla were respectively 86% and 86% in B-II gastrectomy, 90% and 87% in R-Y gastrectomy, and 100% in R-Y hepaticojejunostomy. The therapeutic success rates in all patients and those with an intact papilla were respectively 100% and 100% in B-II gastrectomy, 94% and 92% in R-Y gastrectomy, and 100% in R-Y hepaticojejunostomy. Because the channel diameter was 3.2 mm, stone extraction could be performed with a wire-guided basket in 12 sessions, and wire-guided intraductal ultrasonography could be performed in 8 sessions. As for complications, hyperamylasemia (defined as a rise in serum amylase levels to more than 3 times the upper limit of normal) occurred in 1 patient (7 sessions) with a B-II gastrectomy and 4 patients (19 sessions) with an R-Y gastrectomy. After ERCP in patients with an R-Y gastrectomy, 2 patients (19 sessions) had pancreatitis, 1 patient (21 sessions) had gastrointestinal perforation, and 1 patient (19 sessions) had papillary bleeding. Pancreatitis and bleeding were both mild. Gastrointestinal perforation improved after conservative treatment. CONCLUSION: Short-type SBE is effective for ERCP in patients with a reconstructed intestine and allows most conventional ERCP devices to be used.